2006
DOI: 10.1007/s00436-006-0174-3
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic comparison of allopatric populations of Fasciola hepatica and Fasciola gigantica from European and African bovines using a computer image analysis system (CIAS)

Abstract: The quantification of the different sizes and shapes of Fasciola hepatica and Fasciola gigantica from bovines has been achieved for the first time in natural allopatric populations. Linear measurements, areas and ratios of gravid adults and eggs of F. hepatica (from France and Spain) and F. gigantica (from Burkina Faso) were analysed using a computer image analysis system and an allometric model: (y2m - y2)/y2 = c[(y1m - y1)/y1](b), where y1 = body area or body length, y2 = one of the measurements analysed, y1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 28 publications
4
51
0
7
Order By: Relevance
“…RiveraMarrero et al (1988) also reported that the protein band with a weight of 25 kDa and 30 kDa of fluid F. gigantica ES is a protein with specific properties for acute and chronic fasciolosis in rabbits, cows and sheep. Similar to the results of research Priago (2006) against worms F. gigantica and F. hepatica, the dominant protein profiles appear with a molecular weight of 29.3, 25, and 19 kDa.…”
Section: Profile Protein Antigenic Worms F Gigantica Results Of Westesupporting
confidence: 79%
“…RiveraMarrero et al (1988) also reported that the protein band with a weight of 25 kDa and 30 kDa of fluid F. gigantica ES is a protein with specific properties for acute and chronic fasciolosis in rabbits, cows and sheep. Similar to the results of research Priago (2006) against worms F. gigantica and F. hepatica, the dominant protein profiles appear with a molecular weight of 29.3, 25, and 19 kDa.…”
Section: Profile Protein Antigenic Worms F Gigantica Results Of Westesupporting
confidence: 79%
“…Individual worms were washed extensively in physiological saline solution, identified morphologically as F. hepatica according to existing keys and descriptions of Periago et al (2006) and fixed in 70% ethanol until extraction of genomic DNA. Their codes, host species and geographical origins are listed in Table 1.…”
Section: Parasitesmentioning
confidence: 99%
“…Despite the substantial economic losses caused by Fasciola, estimated at US$ 2 billion per year worldwide (Spithill and Dalton 1998), and the vast distribution of this cosmopolitan parasite (Mas-Coma et al 2003), little attention was given to study the morphometric and/or genetic variation of F. hepatica from different host species and/or geographical localities (Valero et al 2001a, b;Periago et al 2006;Alasaad et al 2007).…”
Section: Introductionmentioning
confidence: 99%